Integrasi Karakter Kedisiplinan Dalam Kegiatan Ekstrakurikuler Pramuka Di MTs Negeri Gemolong - sunardi, sunardi; , Prof. Dr. Bambang Sumardjoko, M.Pd; , Dr. Sumardi, M.Si (2016)
Sunardi. Q 100140083. Integrate discipline character to the scouting movement ekstracuricular in the MTs Negeri Gemolong Sragen Municipality. Thesis. Administration of Education, Post-Graduate Programme, Muhammadiyah University of Surakarta. 2016. The aim of the research is to describe discipline character to the scout ekstracuricular in the MTs Negeri Gemolong Sragen . The research is to explore discipline character in the learning, to explore characteristic of scout ekstraculiculer, and to integreated of discipline character to the scout extracurricular in the MTs Negeri Gemolong Sragen. Method of the research is viii qualitative research. The result of the study is the student's characteristic of their discipline can be seen by the application of how to make the lesson schedule, how to spend the time to study, how to obey the rule of study, and how to keep and care the environment that support the study so that can reach the quality and achievement at school. The Scouting Movement activities includes line of march, cording, pioneering, morse coding, semaphore, and other codes, adventure with signs, and also the exploration with learning-by-doing method. The discipline integration in the scouting movement consists of planing, implementation and evaluation. The forms of the disciplin integration in the scouting movement are giving a good example and role model, activities can ease the students and the teachers or trainers, trains the students to be serious, on time, spend the time to study very well, train to focus and obey the school's rules. The response and expectation of the stakeholders is good and they positively support the activity, because it eases the teachers in making the activities so that they can train the students to be getting better, active in some scouting movement activities as the filed practice. Key word : Integration, discipline character, ekstraculiculer, scouting movement.